แนวทางการบูรณาการพุทธสุขภาวะแบบองค์รวมในชีวิตประจำวัน - (สายัณห์ ปญฺญาวชิโร), พระเทพวชิรวิมล; โพธิ์ชัยหล้า, พรพิมล (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 1 No 3 (2024): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 1 ฉบับที่ 3 : กันยายน - ธันวาคม 2567, 2024)
This article aims to reflect the role of Buddhism in promoting holistic well-being, encompassing the physical, spiritual, and social aspects of life through the integration of Buddhist principles into daily living. Practicing the tenets of Sila (morality), Samadhi (concentration), and Panna (wisdom) contributes to individuals' physical and mental health while also enhancing their ability to handle daily challenges effectively. In terms of physical well-being, maintaining morality, observing moderation in lifestyle, and living in harmony are vital factors that strengthen the body, support good health, and allow individuals to fulfill their daily responsibilities wholeheartedly. For mental well-being, practicing meditation and cultivating loving-kindness (metta) are essential for reducing mental distractions and stress, helping to foster a calm and stable mind. Moreover, Buddhism supports social well-being through the practice of the Four Bases of Social Solidarity (Sangahavatthu): Dana (generosity), which involves giving; Piyavaca (pleasant speech); Atthacariya (conductive to the benefit of others); and Samanattata (impartiality). These practices foster positive relationships within society. On the spiritual dimension, Buddhism emphasizes the development of wisdom and the search for life’s meaning, encouraging individuals to let go of attachment and seek balance between worldly and spiritual happiness. In summary, the application of Buddhist principles in daily life can enhance holistic well-being, leading individuals to live balanced lives and enabling them to confront challenges mindfully and wisely.